New approach for the treatment of neuropathic pain: Fibroblast growth factor 1 gene‐transfected adipose‐derived mesenchymal stem cells. (26th September 2017) - Forouzanfar, F.; Amin, B.; Ghorbani, A.; Ghazavi, H.; Ghasemi, F.; Sadri, K.; Mehri, S.; Sadeghnia, H.R.; Hosseinzadeh, H.
Abstract: Background: Neuropathic pain triggered by peripheral nerve lesion is extremely difficult to manage with current approaches, hence the importance of exploring therapeutic alternatives. Methods: We have analysed adipose‐derived mesenchymal stem cells (AD‐MSCs) and fibroblast growth factor 1 gene‐transfected adipose‐derived mesenchymal stem cells (AD‐MSCs FGF 1 ) on chronic constriction injury (CCI). The mechanical and thermal hypersensitivity were assessed using the von Frey filament, radiant heat and acetone drop tests. Histopathological and apoptotic changes and the level of FGF1, GFAP and TNFα proteins were assessed in the lumbar portion (L4–L6). Moreover, AD‐MSCs FGF 1 were labelled with 99m Tc ‐HMPAO and isolated organ counting were performed upon AD‐MSCs FGF 1 administration. Results: Administration of AD‐MSCs FGF 1 attenuated the CCI‐induced mechanical and thermal hypersensitivity. Spinal structural alterations and apoptosis were decreased in the AD‐MSCs FGF 1 group. The injection of either phosphate‐buffered saline or normal NIH3T3 fibroblasts could not attenuate the behavioural symptoms of neuropathic pain. Increased genetically engineered cells were counted in the injured sciatic nerve and the elevated levels of FGF1 were detected in the spinal tissue. Stem cell therapy lead to decrement the level of the CCI‐induced TNF‐α and GFAP expression. Conclusion: The intravenous administration of AD‐MSCs FGF 1 could be considered as a potential remedy for the management of neuropathic pain. Significance: AD‐MSCs FGF 1 attenuated the CCI‐induced mechanical and thermal hypersensitivity. Spinal structural alterations and apoptosis were significantly decreased in the AD‐MSCs FGF 1 group. Elevated levels of FGF1 were detected in the spinal tissue.